Submissions - Australian Academy of Technological Sciences and Engineering (Melbourne : The Australian Academy of Technological Sciences and Engineering, 1997)
Site includes Academy submissions to government or comments to inquiries related to the interests of the Academy.
Title from home page last updated on 18 Aug. 2002 (viewed on 2 Mar. 2004).
Text and graphics.
Mode of access: Internet via World Wide Web. Available at: http://www.atse.org.au/publications/government/gov-indx.htm
System requirements: Adobe Acrobat for pdf files.
Selected for archiving
Keywords: Science -- Australia; Technology -- Australia